Role of immunotherapy in cancer management - Cherumanalil, Jeeja M.; Pannikkottuthodi, Salwa; Thayyil, Jayakrishnan (International Journal of Basic & Clinical Pharmacology, 2025)
Cancer remains one of the leading causes of mortality worldwide accounting for nearly 20 million new cases and 10 million deaths, prompting continuous research for more effective treatments. In recent years’ immunotherapy has transformed the landscape of cancer treatment, with significant breakthroughs promising more targeted and durable outcomes. Unlike standard treatments, such as surgery, chemotherapy, and radiation, which directly target cancer cells, immunotherapy aims to boost or replace the immune system’s natural ability to fight cancer. Since it is a new mode of therapy most of the practicing doctors are unaware of the details about it. In this context, we conducted a narrative review based on available literature. This article explores the historical background and evolution of immunotherapy, the mechanisms of various immunotherapeutic plans, recent advancements, future directions, and challenges in this field. Our paper focused on, checkpoint inhibitors, chimeric antigen receptor T (CAR-T) cell therapy, oncolytic virus therapy, and cancer vaccines. As the field continues to evolve, collaboration among researchers, clinicians, and patients is essential to drive these advancements and improve outcomes in cancer care.